Attitude Of Teacher Trainees Towards Inclusion Of Special Educational Need (Sen) Children - Kamlesh Nandini Panthri; Dr. Alpana Sharma (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The main objective of the study was to know the attitude of teacher trainees towards inclusion of special educational need (SEN) children. In the presented study the researcher has used the descriptive survey method. A total of 100 B.Ed. Teacher Trainees and D.Ed. Teacher trainee of Jaipur City selected randomly as the sample. A self-administrated attitude scale was used in the study to measure the attitudes of teacher-trainees. The collected data has been done using mean, standard deviation and t-test. The study's findings showed that there is found no significant difference between B.Ed. and D.Ed. teacher-trainees attitude towards inclusion of special educational need children. There is found no significant difference between male and female teacher-trainees attitude towards inclusion of special educational need children.